Suberoylanilide hydroxamic acid affects γH2AX expression in osteosarcoma, atypical teratoid rhabdoid tumor and normal tissue cell lines after irradiation - Blattmann, Claudia; Oertel, Susanne; Thiemann, Markus; Weber, Klaus-Josef; Schmezer, Peter; Zelezny, Otto; Lopez Perez, Ramon; Kulozik, Andreas; Debus, Jürgen; Ehemann, Volker (Strahlentherapie und Onkologie, 2012)
PurposeOsteosarcoma and atypical teratoid rhabdoid tumors are tumor entities with varying response to common standard therapy protocols. Histone acetylation affects chromatin structure and gene expression which are considered to influence radiation sensitivity. The aim of this study was to investigate the effect of the combination therapy with the histone deacetylase inhibitor suberoylanilide hydroxamic acid (SAHA) and irradiation on atypical teratoid rhabdoid tumors and osteosarcoma compared to normal tissue cell lines.MethodsClonogenic assay was used to determine cell survival. DNA double-strand breaks (DSB) were examined by pulsed-field electrophoresis (PFGE) as well as by γH2AX immunostaining involving flow cytometry, fluorescence microscopy, and immunoblot analysis.ResultsSAHA lead to an increased radiosensitivity in tumor but not in normal tissue cell lines. γH2AX expression as an indicator for DSB was significantly increased when SAHA was applied 24 h before irradiation to the sarcoma cell cultures. In contrast, γH2AX expression in the normal tissue cell lines was significantly reduced when irradiation was combined with SAHA. Analysis of initial DNA fragmentation and fragment rejoining by PFGE, however, did not reveal differences in response to the SAHA pretreatment for either cell type.ConclusionSAHA increases radiosensitivity in tumor but not normal tissue cell lines. The increased H2AX phosphorylation status of the SAHA-treated tumor cells post irradiation likely reflects its delayed dephosphorylation within the DNA damage signal decay rather than chromatin acetylation-dependent differences in the overall efficacy of DSB induction and rejoining. The results support the hypothesis that combining SAHA with irradiation may provide a promising strategy in the treatment of solid tumors.